2019
DOI: 10.3390/plants8100431
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Priming Regulates Morpho-Physiological Growth and Oxidative Metabolism in Maize under Drought Stress

Abstract: Seed priming with silicon (Si) is an efficient and easy method to regulate plant tolerance against different abiotic stresses. A pot experiment was conducted to examine the Si-mediated changes in oxidative defense and some vital physio-biochemical parameters of maize under a limited water supply. For this purpose, two maize varieties (Pearl and Malka) with different Si priming treatments (0, 4 mM, 6 mM) were grown under a control and 60% field capacity for three weeks. At 60% field capacity, significant reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
88
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 52 publications
18
88
0
3
Order By: Relevance
“…4c, the exposure to B-32°C induced a more significant oxidative damage in untreated plants than in Si-fertilized plants, indicating that Si application can prevent the structural and functional deterioration of cell membranes by protecting them from ROS toxicity and reducing oxidative stress. These findings are in accordance with the studies of Rubinowska et al (2014), Shekari et al (2017), and Parveen et al (2019), who stated that the Si treatment reduced the permeability of the membranes by stimulating the synthesis of antioxidant enzymes, which deactivate the H 2 O 2 responsible for the peroxidation of cell lipids. Moreover, these authors suggested that Si can act in the stability of cell membranes through changes in the ratio of unsaturated and saturated fatty acids, maintaining the integrity and functionality of plasmatic membranes.…”
Section: Antioxidant Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…4c, the exposure to B-32°C induced a more significant oxidative damage in untreated plants than in Si-fertilized plants, indicating that Si application can prevent the structural and functional deterioration of cell membranes by protecting them from ROS toxicity and reducing oxidative stress. These findings are in accordance with the studies of Rubinowska et al (2014), Shekari et al (2017), and Parveen et al (2019), who stated that the Si treatment reduced the permeability of the membranes by stimulating the synthesis of antioxidant enzymes, which deactivate the H 2 O 2 responsible for the peroxidation of cell lipids. Moreover, these authors suggested that Si can act in the stability of cell membranes through changes in the ratio of unsaturated and saturated fatty acids, maintaining the integrity and functionality of plasmatic membranes.…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…3b) content in plant tissues can be a precursor of a highly reactive oxygen species (Ślesak et al 2007). The accumulation of H 2 O 2 affects the structure and integrity of plasma membranes by influencing the stress-dependent peroxidation of membrane lipids (Liang et al 2006(Liang et al , 2007Parveen et al 2019). The present findings suggest that the increased CAT, POD, and APX activity in Si-treated plants (10 mM SiK®) was beneficial to the lower levels of H 2 O 2 under high temperature conditions (B-32°C), as compared to control plants (0 mM SiK®).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Water deficit and suboptimal temperature are adverse environmental factors that impose drastic effects on crop plants [ 2 , 22 ]. Maize is comparatively more sensitive to water scarcity and low temperature conditions particularly at the early stages of plant growth [ 2 , 25 , 26 , 27 ]. The present study indicated that all the maize shoot growth attributes were severely hampered by drought, chilling, and combination of drought + chilling stresses ( Figure 1 and Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both chilling and drought stresses have been reported to cause the oxidative damage in plants by the overproduction of ROS in cells [ 2 , 9 , 18 , 32 , 33 ]. However, plants have developed a complex antioxidative defense system, which consists of non-enzymatic and enzymatic components to overcome the excessive production of ROS [ 19 , 26 , 34 , 35 ]. The balance between ROS generation and antioxidants (enzymatic and non-enzymatic) is critical in all plant species under stress conditions [ 12 , 29 , 33 , 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several species, Si appears to increase the level of soluble sugars under salt and drought stress (rice: Yang et al, 2019;wheat: Alzahrani et al, 2018;okra: Abbas et al, 2015;tobacco: Hajiboland et al, 2017), however, Kang et al (2016) reported decreased soluble sugar content in osmotically-stressed Zygophyllum xanthoxylum. Although in general Si appears to increase glycine betaine levels (Abbas et al, 2015;Saleh et al, 2017;Ahmad et al, 2019;Al-Huqail et al, 2019), decreases have been reported for drought-stressed maize (Parveen et al, 2019) and salt-stressed borage (Torabi et al, 2015). There is a trend for Si to increase polyamine levels under drought and salt-stress Yin et al, 2016;Ali et al, 2018;Yin et al, 2019).…”
Section: Water Statusmentioning
confidence: 96%